Answer:
The answer is option A. 117
Explanation:
The general solution of the quadratic equation is:
![x=(-b \pm √(b^2-4ac) )/(2a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/mnrp18zc5kjqikys59crursg6mp5jyic72.png)
The given equation is x2 + 9x − 9 is expressed as minus 9 plus or minus the square root of r, all over 2
Comparing to the general solution
∴ r = determinant = b² - 4 a c
From the given equation: a = 1 , b = 9 and c = -9
∴ r = 9² - 4 * 1 * (-9) = 81 + 36 = 117
The answer is option A. 117